両側頰粘膜に発生した憩室様病変の１例 - 國井, 俊介; 須貝, 彩夏; 小林, 武仁; 坂本, 雄哉; 笹原, 庸由; 飯野, 光喜 (日本口腔外科学会雑誌, 2024)
A diverticulum is a pouch structure projecting outward from the canal of the gastrointestinal tract. This lesion can occur at any site in the gastrointestinal tract and is known to be found more frequently in the colon. However, it rarely occurs in the oral cavity. We report a case of a diverticulum-like lesion of the bilateral buccal mucosa. A-84-year-old man was referred to the Department of Dentistry and Oral Surgery at Okitama Public General Hospital by his family dentist due to the identification of small pouches containing stagnant food residue. We found two pouches bilaterally located below the parotid papilla. The right lesion was 5mm in diameter and 6mm in depth; the left lesion was 9mm in diameter and 8mm in depth. The luminal surfaces of the pouches were smooth mucosa, and normal in color. MRI showed small pouches in the bilateral buccal mucosa. No communication with the parotid duct was noted. Based on a clinical diagnosis of a diverticulumlike lesion of the buccal mucosa, the lesion was surgically resected under general anesthesia. After the surgery, the bilateral small pouches disappeared and the food residue improved. Three years after the surgery no abnormalities or signs of recurrence have been detected.